Recent development in catalyst and reactor design for CO2 reforming of alcohols to syngas: A review - Nornasuha, Abdullah; Nurul Aini, Razali; Setiabudi, Herma Dina (Elsevier Ltd, 2022)
Global energy demand has had a significant impact on the Green House Gases (GHGs) emission, which have harmful effects on the environment and human health. Catalytic CO2 reforming of biomass-derived alcohols converted into syngas is regarded as a viable option for reducing GHGs. Even though this is sustainable and ecologically beneficial for utilizing value-added biomass, little research has been done on the topic. Due to the high reaction temperature, metal sintering and coke formation have been widely reported as the major challenges in the CO2 reforming process. These conditions could reduce the catalyst efficiency and cause the reactor system to shut down. To address these issues, this article provides a review of the current catalyst and reactor design development for CO2 reforming of methanol, ethanol, glycerol, and butanol to generate synthetic gas. Thermodynamic analysis, catalyst performance, optimizing reaction parameters, and future potential catalyst design are also covered.